Integrating an Adapted, Low-Intensity Program to Promote Early Childhood Development in Routine Health Visits in Rural India: A Feasibility Study. Issue 4 (May 2020) - Shah, Reshma; Gustafson, Erika; Dhaded, Sangappa; Herekar, Veena; Metgud, Deepa; Mastiholi, Spoorthi; Kim, Hajwa; Goudar, Shivaprasad; Atkins, Marc
ABSTRACT: Objective: More than 200 million children younger than the age of 5 years fail to reach their full developmental potential in low- and middle-income countries (LMICs). The purpose of this study was to describe the feasibility of integrating a brief program to promote early childhood development within a health care setting serving a predominantly rural population in India. Methods: We conducted a prospective, noncomparative, mixed-methods study. An adapted parent-directed program was administered to caregivers of 2- to 6-month-old children while waiting for their health care provider. Caregivers completed baseline and 4-week follow-up surveys. Thematic analyses and generalized equation estimates were used for analyses in the following feasibility indicators: acceptability, demand, implementation and practicality, and limited efficacy testing. Results: Forty-seven caregivers were recruited; most were women (98%) and had equal to or less than 12 years of schooling (61%). Forty-six of 47 participants completed the follow-up at 1 month. Three administrators were trained to deliver the program over the course of 2 days. Caregivers perceived a need for the program and found the content and structure of the program useful. However, there were important suggestions for improvement, including greater visual content and dissemination to nonparental caregivers and fathers. Significant increases were seen on self-reported parenting behaviors regarding a child's caregiving environment. Conclusion: Our findings support the feasibility of integrating an adapted, low-intensity program in a primary care setting in India, but important adaptations and considerations will need to be addressed before effectiveness testing on a wider scale. We discussed implications for offering sustainable population-level interventions to promote early childhood development in LMICs. Abstract : This article has supplementary material on the web site: www.jdbp.org.